Perceived Stress, Coping Behaviors, Social Support and Subjective Health among Unmarried Older Adults - Noradilah, Md Nordin; Martin, Peter; Bishop, Alex J. (Human Resource Management Academic Research Society (HRMARS), 2023)
The purpose of this study was to examine coping behaviors and social support as mediators and moderators between perceived stress and subjective health among older adults. A sample of 227 unmarried older adults was recruited. A hierarchical regression analysis was performed in order to analyze mediator and moderator effects of coping behaviors and social support. The results suggest that problem-focused coping and social support partially mediated the association between perceived stress and subjective health. We conclude that stress in older adults should be minimized and effectively managed to prevent negative effects on subjective health. Intervention programs focusing on problem-focused coping and social support should be developed for older adults.